2008
DOI: 10.1089/jwh.2007.0544
|View full text |Cite
|
Sign up to set email alerts
|

Are Depressive Symptoms Associated with Cancer Screening and Cancer Stage at Diagnosis among Postmenopausal Women? The Women's Health Initiative Observational Cohort

Abstract: Background: Women with depressive symptoms may use preventive services less frequently and experience poorer health outcomes. We investigated the association of depressive symptoms with breast and colorectal cancer screening rates and stage of cancer among a cohort of postmenopausal women. Methods: In The Women's Health Initiative Observational Study, 93,676 women were followed on average for 7.6 years. Depressive symptoms were measured at baseline and at 3 years using the 6-item scale from the Center for Epid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
3
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 31 publications
2
32
3
1
Order By: Relevance
“…For example, a delay of several months for an abnormal mammogram may be clinically more significant than several months of delayed resolution for abnormal Pap tests. However, our results contrast from studies of cancer screening tests reporting depression being associated with less screening mammography, 2,25 but not with fewer Pap tests. Prior research found conflicting effects between the relationship of cancer screening behavior and depression.…”
Section: Discussioncontrasting
confidence: 99%
“…For example, a delay of several months for an abnormal mammogram may be clinically more significant than several months of delayed resolution for abnormal Pap tests. However, our results contrast from studies of cancer screening tests reporting depression being associated with less screening mammography, 2,25 but not with fewer Pap tests. Prior research found conflicting effects between the relationship of cancer screening behavior and depression.…”
Section: Discussioncontrasting
confidence: 99%
“…Higher levels of depressive symptomatology were found to be associated with reduced rates of breast cancer screening behaviors in women. [44][45][46][47] On the other hand, similar associations were not found between cervical cancer screening and depressive symptoms, 45 nor was a direct association found for colorectal cancer in women and men. 48 When the analysis was performed by restricting to those participants with ''No VI'' and ''Some VI'' by excluding the blind participants, the direct effect of VI on all-cause mortality had the same directionality and was weakened; HR decreased from HR ¼ [1.11, 1.74], P < 0.05.…”
Section: Discussionmentioning
confidence: 99%
“…(54) However, while the symptom windows for CES-D and PSS are relatively short, gauging symptoms within the prior week or month, numerous studies have linked these measures with long-term health outcomes. (5558) Repetition of the study with more comprehensive or robust assessment tools and periodic reassessments may alter the observations. The REGARDS study is currently re-examining all members of the cohort, and in a future effort it may be possible to determine if interval changes in reported depressive symptoms may be associated with sepsis incidence.…”
Section: Discussionmentioning
confidence: 99%